ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGIES IN DEVELOPING STUDENT CHARACTER EDUCATION - Haluti, Farid; Mufarrihah, Anik; Nimim (JURNAL PENDIDIKAN GLASSER, 2024)
Islamic religious education teachers' strategies in developing character education in students may involve a deep understanding of Islamic religious values that include ethics, morals and manners. These teachers may understand that strong character in accordance with Islamic teachings can form individuals who are religious, responsible, disciplined and honest. The purpose of this study is to analyze the role and strategies used by Islamic Religious Education teachers in developing students' character education at SDN Bulungkobit. The method used is qualitative type, where data collection is done through documentation, interviews, and observation. Data analysis was carried out through the stages of collecting data, reducing data, presenting data and concluding and verifying. From the results of the study, it can be concluded that the strategies carried out by Islamic Religious Education teachers in shaping character are through integration, through daily activities which include modeling, habituation, reprimand, advice, and environmental conditioning that supports the formation of student character